Testes para avaliar o potencial fisiológico de sementes de beterraba - Silva, Josué Bispo da [UNESP] (2006)
The use of vigor tests is essential to evaluate the physiological potential of seed lots produced and selled by a company. The work, separated in two stages, aimed to study different vigor tests to evaluate the physiological potential of beetroot seeds. With base in the results, it was concluded that EA, EASS-20, EASS-40 and DC tests can be used to evaluate the physiological potential of beet seeds; the use of solutions presents advantage on the traditional procedure; the adjustment of seed MC in the controlled deterioration test would be done by the method of humid substratum.